A novel high‐gain bidirectional DC–DC converter for EV onboard charger applications. (15th March 2022) - Krishna, Bekkam; Lithesh, Gottapu; Karthikeyan, V.
Abstract: In electric vehicle (EV) onboard applications, the bidirectional DC‐DC converter is proposed in this paper to interface low terminal voltage battery with DC bus of the motor. The proposed bidirectional DC–DC converter is configured based on a ladder switching network of inductors and a capacitor. Due to this configuration, the proposed converter has a simple structure, and it can archive high voltage gain with fewer components. A detailed comparative analysis is presented to verify the uniqueness and superiority of the proposed topology. Furthermore, the detailed steady‐state analysis and working principles are presented in this paper. Finally, the 300‐W prototype is built, and the experimental results are presented to verify the performance and feasibility of the proposed bidirectional converter. Abstract : In this paper, the bidirectional DC–DC converter is proposed to interface low terminal voltage battery with DC bus of the motor for electric vehicle applications. The proposed bidirectional DC–DC converter is configured based on a ladder switching network of inductors and a capacitor. Due to this configuration, the proposed converter has a simple structure, and it can archive high voltage gain with fewer components.